Optical Absorptivity Enhancement of SiO2 Thin Film by Ti and Ag Additive - Prasopporn Junlabhut; Sakoolkarn Boonruang; Wisanu Pecharapa (My University, 2013)
This paper presents the visible optical absorptivity enhancement of SiO2 thin films by Ti and Ag additive. SiO2 thin films were prepared on glass substrate by sol-gel technique. Methacryloxy propyl trimethoxysilane (MAPTMS), Titanium isopropoxide (TiP) and Silver nitrate were used as precursors. MAPTMS was dissolved in absolute ethanol with various Ti and Ag content. The physical properties of as-prepared films were characterized by X-ray diffraction (XRD) and Transmission electron micrograph (TEM). The effects of Ti and Ag addition on optical properties were investigated from its optical absorption measured by UV-VIS Spectrophotometer (UV-VIS). XRD patterns shows the formation of TiO2 and Ag in thin film. The effect of Ti and Ag additive on SiO2 thin films were scrutinized by mean of the optical absorption in visible region. XRD and TEM results disclose the existence of TiO2 and Ag nanoparticles in the as-prepared films. It can be observed that the improvement in optical absorption in both UV and visibl e region can be efficiently accomplished by the incorporation of Ti and Ag into SiO2 films.
Keywords: Molar absorptivity; Silver nitrate; TiO2 Photocatalysis and Solar Cells